2020
DOI: 10.3389/fgene.2020.00327
|View full text |Cite
|
Sign up to set email alerts
|

Expressing a Target Mimic of miR156fhl-3p Enhances Rice Blast Disease Resistance Without Yield Penalty by Improving SPL14 Expression

Abstract: Expressing a Target Mimic of miR156fhl-3p Enhances Rice Blast Disease Resistance Without Yield Penalty by Improving SPL14 Expression. Front. Genet. 11:327.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 62 publications
0
29
0
Order By: Relevance
“…Besides, some sRNAs also coordinate responses to biotic stressors with the regulation of growth and development. For examples, miR156-OsIPA1 module negatively regulates rice resistance to M. oryzae and it also regulates seed dormancy and germination; miR396-OsGRFs modules negatively regulate rice resistance to M. oryzae and they also regulate plant height, leaf morphology and seed size (Guo et al 2016;Tang et al 2018;Zhang et al 2018a;Zhang et al 2020). Therefore, sRNA pathway may act as a part of innate immunity to tightly coordinate rice growth, development, and immunity, thus could be used as a candidate to balance the trade-off between yield and resistance in rice breeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, some sRNAs also coordinate responses to biotic stressors with the regulation of growth and development. For examples, miR156-OsIPA1 module negatively regulates rice resistance to M. oryzae and it also regulates seed dormancy and germination; miR396-OsGRFs modules negatively regulate rice resistance to M. oryzae and they also regulate plant height, leaf morphology and seed size (Guo et al 2016;Tang et al 2018;Zhang et al 2018a;Zhang et al 2020). Therefore, sRNA pathway may act as a part of innate immunity to tightly coordinate rice growth, development, and immunity, thus could be used as a candidate to balance the trade-off between yield and resistance in rice breeding.…”
Section: Discussionmentioning
confidence: 99%
“…More than 70 miRNAs respond to M. oryzae or its elicitors (Li et al 2019c). Among these miRNAs, five have been identified as positive regulators in rice blast resistance, namely miR160a, miR162a, miR166k-h, miR398b, and miR7695, whereas eight have been identified as negative regulators, namely miR156, miR164a, miR167d, miR169a, miR319b, miR396, miR1873, and miR444b.2 (Chandran et al 2018;Li et al 2020a;Li et al 2019b;Li et al 2014;Li et al 2017;Salvador-Guirao et al 2018;Sanchez-Sanuy et al 2019;Wang et al 2018b;Xiao et al 2017;Zhang et al 2018b;Zhang et al 2020;Zhao et al 2020;Zhou et al 2020). Obviously, many miRNAs play a role in regulating rice-M. oryzae interactions.…”
Section: Small Rnas In Rice-m Oryzae Pathological Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed that a substantial fraction of the miRNAome is regulated during M. oryzae infection, and/or treatment with M. oryzae elicitors in rice plants (Baldrich et al., 2015 ; Campo et al., 2013 ; Li et al., 2016 ). However, only few miRNAs with a function in blast resistance have been reported, which include positive (miR7695, miR160, miR162, miR398 and miR166k‐166h) and negative (miR156, miR164, miR167, miR169, miR319, miR396, miR442 and miR1873) regulators of immune responses (Campo et al., 2013 ; Chandran et al., 2019 ; Li et al., 2014 , 2017 , 2020b ; Salvador‐Guirao et al., 2018b ; Sánchez‐Sanuy et al., 2019 ; Wang et al., 2018 ; Zhang et al., 2018b , 2020 ; Zhao et al., 2020 ; Zhou et al., 2019 ). Clearly, the involvement of miRNAs in rice immunity has only begun to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of miR812w enhances resistance by regulating the methylation of target genes ( Campo et al, 2021 ). In contrast, miR156 ( Zhang et al, 2020 ), miR159 ( Chen et al, 2021 ), miR164a ( Wang Z. Y. et al, 2018 ), miR167 ( Zhao et al, 2019 ), miR168 ( Wang et al, 2021 ), miR169 ( Li et al, 2017 ), miR319b ( Zhang et al, 2018 ), miR396 ( Chandran et al, 2019 ), miR439 ( Lu et al, 2021 ), and miR1873 ( Zhou et al, 2020 ) negatively regulate rice resistance to blast fungus by suppressing the expression of their target genes.…”
Section: Introductionmentioning
confidence: 99%